Penentu faktor peramal pengekalan pekerjaan dalam kalangan klien AADK - Muhammad Ajib Abd Razak,; Rozmi Ismail,; Noh Amit,; Norhayati Ibrahim,; Faizah Isa, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Occupation is the most important element in changing the quality-of-life continuity and the recovery of drug addicts. This study aimed to measure the level of employment sustainability among ex-clients from the National Anti-Drug Agency (AADK). This study used a quantitative approach with a cross-sectional design. A total of 130 AADK ex-clients who were in employment were selected as respondents for this study. Our findings show that the majority of AADK ex-clients can survive relatively well enough for between 1 to 2 years depending on the factors of wages, work environment, interests and skills. The finding of this study implies that former clients tend to remain only 1 to 2 years in employment if their wages and jobs are not in line with their will. The findings also found that there was a significant relationship between the job-person fit and job satisfaction with motivation. Hence, this study is capable to modify the perceptions and views of employers towards clients' initiative for being persistent at the workplace as well as improving existing policies in providing incentives to clients for being consistent on the job.